School Resource Officer (Sro) Competencies In Dealing With High School Students Criminal Behavior Based On SPPTP - Mat Aris, Azizi; Hasan, Shahizan; Mohd Yusoff, Azlina; M. Luddin, Abu Bakar; Wari, Wanita (Universiti Sains Malaysia, 2016)

(untitled)
This study focuses on the competencies of School Resource Officers (SRO) on dealing with the crime prevention system and the formation of the personality development using Sistem Pencegahan dan Pemantauan Tingkah laku Pelajar (SPPTP) or Prevention and Monitoring System on Students Behavior. The misconduct of students in secondary schools was identified and it was examined that the causes of serious offenses among school students had shown the tendency towards criminal behavior in schools. 14 schools in Middle Zone of Kedah were selected and 28 SRO were given the resposibilities to monitor the students according to regulation issued by the Inspector General of Police, Malaysia, IGP 96/19, in May 2014 Administrative Instruction No. 14/2004 regarding the misconduct of school students towards criminal behavior in schools.